He, Ne, Ar stepwise crushing data on basalt glasses from different segments of Bouvet Triple Junction - Buikin, Alexei I.; Hopp, Jens; Trieloff, Mario (Geochemistry international, 2017)
Here we present the first data on He, Ne, Ar isotopic and elemental composition in fluid phases of tholeiitic chilled glasses from the Bouvet Triple Junction (BTJ). The chilled glasses from several dredging stations situated at different segments of BTJ have been investigated: Spiess Ridge, Mid Atlantic Ridge (MAR) and in a valley of the Southwest Indian Ridge (SWIR). The data allow to distinguish within BTJ three segments characterized by different geochemical behavior of He, Ne and Ar. MAR and Spiess samples contain MORB-like helium and neon while SWIR is characterized by addition of plume type He and Ne. The strong atmospheric contamination is typical of all segments, but for MAR it is less pronounced. The Ne-Ar isotope systematics suggests that the atmospheric component was most probably introduced into the mantle source of the fluids with fragments of oceanic crust/sediments.